TINGKAT KINERJA PETANI PADI SAWAH DI KELURAHAN MEKAR SARI KABUPATEN KONAWE - Kadek Riyanti Cahyani Putri; Dasmin Sidu; Mardin Mardin (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2025)
The objective of this study is to ascertain the performance level of wet-rice farmers in Mekar Sari Village, Konawe Regency. The population of this study consists of all rice farmers in Mekar Sari Village, with a total of 231 individuals who are members of 11 farmer groups. The 11 farmer groups are as follows: Bakti Tani, Wanasari, Sumber Tirta Jaya, Bendung Jaya, Catur Lomena Karya, Harapan Jaya, Jaya Abadi, Sri Lomena, Sumber Merta, Tirta Mulya, and Bunga Mekar. The sample size was determined by the Slovin formula with a margin of error of 10%, resulting in a final sample of 70 farmer respondents. The research sample was obtained through the implementation of a proportional random sampling method. Each farmer group will be represented by a subset of group members, with the number of representatives ranging from six to seven. The data were collected using a variety of research methods, including survey techniques, a literature review, documentation, and interviews guided by a questionnaire. The research variable is defined as the level of farmer performance, which is comprised of three components: productivity, input efficiency, and timeliness. The collected data is then subjected to descriptive analysis. The findings indicated that the performance of wet-rice farmers in Mekar Sari Village can be characterized as highly satisfactory. The productivity of farmers cultivating wet rice has been documented as 4 tons per hectare. The temporal parameters of planting, irrigation, and harvesting have been found to adhere to the recommendations stipulated by the local Field Agricultural Extension Officer. Subsequently, the application of seeds and fertilizers should be executed in accordance with the recommendations stipulated by the Field Agricultural Extension Officer. Therefore, it is imperative to ensure the optimal production outcomes through the continuous maintenance and enhancement of farmers' performance in rice paddy farming.